Pengaruh Aktiva Pajak Tangguhan Dan Beban Pajak Tangguhan Terhadap Earnings Response Coefficient - Abdul Malik; Anita Asnawati; Neneng Sri Suprihatin (Universitas Serang Raya, 2023)
The purpose of this study is determine the influence of deferred tax assets and deferred tax expense on earnings response coefficient in partially. The study method used in this study was associative descriptive method. This type of study was a type of causality research. The population in this study were property and real estate manufacturing companies listed on the Indonesian Stock Exchange (IDX) for the 2016-2020 period. The sample was selected by purposive sampling method. The number of samples in this study were 7 companies for 5 year, so the selected sample was 35 samples. By testing classical assumptions, and testing hypotheses and statistical analysis, namely multiple linier regression analysis. Based on the results of the study, it can be concluded that: 1) Deferred tax assets have no effect on earnings response coefficient, 2) Deferred tax expense have no effect on earnings response coefficient.